Competing transmission of multiple infectious agents in multiplex networks - Yu, Jie (2016)
Due to the rapid growth of computer network, idea, virus are spreading extremely fast on the internet. As we known, there are several of various infectious diseases in the biological life and virus in the online world. But in fact, compared to the transmission of infectious disease, those infectious viruses spreading in complex network have similar patterns and model [1]. The main purpose of this project is study the transmission of infectious agents in complex networks, in order to find out and discuss the model that the infectious agent transmitted.